Total Price:

There are no items in this cart.
Continue Shopping

Integral of cosec-1 x 

In above it is cosec inverse x.

3 years ago


Answers : (1)


Dear Pankaj,

Take cosec^-1 x=sin^-1 1/x then see where do the function changes its value from one integer to another within the limits and then integrate.

Best Of luck

Cracking IIT just got more exciting,It s not just all about getting assistance from IITians, alongside Target Achievement and Rewards play an important role. ASKIITIANS has it all for you, wherein you get assistance only from IITians for your preparation and win by answering queries in the discussion forums. Reward points 5 + 15 for all those who upload their pic and download the ASKIITIANS Toolbar, just a simple  to download the toolbar….

So start the brain storming…. become a leader with Elite Expert League ASKIITIANS


Aman Bansal

Askiitian Expert

3 years ago

Post Your Answer

More Questions On Integral Calculus

Ask Experts

Have any Question? Ask Experts

Post Question

Answer ‘n’ Earn
Attractive Gift
To Win!!!
Click Here for details
integrate the following integral ∫ x sqrt(x+2) dx
Ans: Hello Student, Please find answer to your question below
Jitender Singh 9 months ago
integration root cos2A/sinA=
Ans: Hello student, Please find the answer to your question below
Jitender Singh 8 months ago
find the area bounded by the curves x = y 2 and x = 3 – 2y 2
Hi, point of intersection of two curves (1,1) and (1,-1) Area bounded = Integration of [ (3-2y 2 ) – y 2 ] from y = -1 to y = 1 The integration come out to be 4 units....
Shobhit Varshney 6 months ago
The area bounded will be given by point of intersection will be y 2 = (3 – 2y 2 ) => y 2 =1 => y = +1 and -1 so limit of integration will be -1 to +1 So just solve this definite...
Nishant Vora 6 months ago
If the equation z 3 +(3+i)z 2 -3z- (m+i)=0, where m is a real number, has at least one real root, then m can have the value equal to Answer: 1 or 5
Let a,b,c be the roots. If a is real, (b,c are conjugates) a+b+c=3+i abc=m+i ab+bc+ca=-3 Use this information and solve for m....
Ravi 6 months ago
mycroft holmes 6 months ago
which number has the same property as the following numbers? (363,489,579) a)281 b)382 c)471 d)562
Hello student, The numbers given to us are 363, 489, 579 By seeing these three numbers, we can judge that the sum of the digits in all three cases is 3 as, 363 = 3 + 6 + 3 = 12 = 1+2 = 3....
Latika Leekha 21 days ago
the answer comes to be C because of the addition results in the number 3
akshat 8 days ago
the answer is c because it is the only multiple of 3
Shubham Singh 7 days ago
if angle A=90 2[r+R]=?
Hello Student, Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
Arun Kumar 10 months ago
Amazing sir :) Thanks
Leo Pixie 10 months ago
View all Questions »